Integrated chebyshev bandpass filter and notch filter with reconfigurable capabilities for wideband wireless communication - Mohamad Ariffin Mutalib (2018)
Microwave bandpass filter with wideband passband has been attracting a lot of interests of the researcher to employing different methods and techniques. However, some existing radio systems that use narrow band signals, such as IEEE 802.11a WLAN in the band 5.2 GHz and 5G WiFi has operating band from 5.15-5.85 GHz can cause an interference with the wideband systems (3-6 GHz). Moreover, to overcome the problem of very large numbers of standard to mitigate the strong interference signals, the flexibility device is really required. To overcome the problem, electronically reconfigurable bandpass filter and notch response will be introduced with tunable capabilities to solve the limitation of fixed pre-defined method. Therefore, this thesis presents new techniques for the design of microwave bandpass filter at 3 to 6 GHz which cover wideband with a fractional bandwidth of about 66.15%. The reflection coefficient is better than -16 dB and transmission coefficient is less than -0.9 dB. This filter was constructed by using microstrip short circuit stubs bandpass filter. This thesis also discusses about enhanced selectivity of bandpass filter by replacing the first short circuited stub with two sections of open circuited stub, the transmission zeros can be obtained at the desired frequency. This method is very useful to increase the selectivity where the number of elements can be reduced and also maintaining the overall performance. Varactor diode is placed at the end of J-shaped open circuited stub. Then the notch structure will be integrated with the bandpass filter in order to provide high attenuation at -21 dB with narrow bandwidth with 0.28 % FBW and high Q-factor with 706. This structure is very useful for wireless systems as it can be easily integrated with other planar devices. Advanced Design System (ADS) software was used to simulate the design from circuit element to physical momentum realization. The experimental results showed good agreement with the simulated results. The benefits of the integrated bandpass filter and notch structure are the improved performance, easier to fabricate and high Q-factor. This new design of microwave filter is considered suitable and an alternative solution for wireless, radar and also 5G application without any addition of external components in the cascaded structure